Study on Potential Carbon in Pocut Meurah Intan Forest Park, Aceh Province - Syakur*, Syakur; Sugianto, Sugianto; Basri, Hairul; Fadhli, Rahmad (Graduate School of Universitas Syiah Kuala, 2023)
The existence of forest park areas plays an essential role as carbon sequestration can reduce the concentration of greenhouse gases in the atmosphere. Analysis of carbon potential is essential in determining the amount of available carbon potential. This study aims to analyze the carbon potential in the forest park area Pocut Meurah Intan Forest Park. The study used a descriptive method with the sampling technique of the path system. Data analysis and calculation of carbon potential using allometric equations to calculate the total biomass. Spatial analysis using Arc.GIS 10.4 software and the carbon content analysis was carried out using the ashing method. The results showed that the potential carbon stock of Pocut Meurah Intan Forest Park was 640,282 tons. The carbon potential is the carbon stored above the ground in the form of carbon from above-ground biomass (trees, poles, saplings, undergrowth) and organic matter (necromass and litter). The highest carbon potential was found in the secondary dryland forest land cover with a total of 555,204 tons or 167.6 tons ha1 , followed by shrubs of 78,949 tons or 33.3 tons ha -1 , and the lowest potential carbon stock was found in the open field of 303 tons or 2.8 tons ha-1 . The increase in land cover in secondary dryland forests causes increased carbon storage. The low potential for carbon stocks is due to land clearing and a small number of stands, resulting in a decrease in potential carbon stocks.